A drilling wellbore pressure calculation model considering the effect of gas dissolution and suspension - Zhang, Wenbo; Xue, Xianbo; Zhang, Chengcheng; Qu, Yue; Ke, Ke; Pan, Shaowei; Zeqin Li; Zhang, Jianbo (Frontiers in Earth Science, 2022)
The complex formation pressure system and diverse formation fluid components during deepwater and deep drilling make it easy for gas intrusion accidents to occur. The dissolution and suspension of the intruded gas in the drilling fluid and the difference between the gas-liquid phase distribution characteristics and the gas-water two-phase flow characteristics in the wellbore lead to errors in the calculation of wellbore pressure and overflow assessment after gas intrusion. In this paper, a wellbore multiphase flow model considering gas dissolution and suspension is established, and the influence of gas dissolution and suspension in drilling fluid on the multiphase flow in the wellbore during overflow, well shutdown and compression is analyzed with the model calculation results. When free gas is present in the wellbore, the higher the drilling fluid density and yield stress, the higher the gas limit suspension concentration. After the gas intrusion shutdown, when there are suspended and transported gases in the wellbore, the rate of pressure increase in the wellbore decreases after the shutdown, and the volume fraction of free gas decreases the longer the shutdown time, and eventually all the gases will be suspended in the drilling fluid. During the pressure process, gas dissolution leads to an increase in the peak pressure in the wellbore and a delay in its occurrence; gas suspension leads to a decrease in the peak pressure in the wellbore and a delay in its occurrence. This paper establishes a multiphase flow calculation model for the wellbore considering both gas dissolution and suspension, which is a guideline for the calculation of wellbore pressure after gas intrusion.